Regional financial performance profile of East Kalimantan Province, Indonesia - Juliansyah Roy; Agus Iwan Kesuma; Yesi Aprianti (Technium Social Sciences Journal, 2020)
As a consequence of the implementation of regional autonomy, the government is required to carry out its duties properly and transparently. The implementation of regional autonomy requires a decentralized system that is transparent, effective, efficient, and accountable to the wider community. This study needs to be carried out aimed at providing an overview of the regional financial performance of East Kalimantan Province based on regional financial ratios. The analysis model that we use is through quantitative descriptive analysis with a series of regional financial ratio analysis models. The secondary data is based on time series for 10 periods. The findings that reveal the degree of fiscal decentralization highlight the ability of the East Kalimantan provincial government to increase PAD. From the analysis of the ratio of regional financial dependence, determining the dependence of regional finances on the central government is still high. The analysis of the ratio of regional financial independence is very high, where the role of the central government has begun to decrease. In the ratio of the effectiveness of PAD, it is very effective in realizing PAD revenue against the target. Then, the results of the efficiency ratio of PAD are classified as efficient because they use the acquisition cost of PAD.